The localization of estrogen receptor alpha and its function in the ovaries of postmenopausal women. - Jacek Brodowski (Folia Histochemica et Cytobiologica, 2008)
The localization of estrogen receptor alpha (ERalpha) in the ovaries of postmenopausal women is a very up-to-date topic in the aspect of using estrogens therapy in the clinical situations of different type. In ovaries of reproductive age women ERalpha is present in ovary stroma, theca and granulosa cells, ovary surface epithelium (OSE) and in corpus luteum. The ovaries of postmenopausal women are smaller than those of women at the reproductive age, the division into cortex and medulla gets blurred, the ovaries have no follicles any longer, and the stroma is mainly composed of fibrous connective tissue, corpora albicantia, nerves, and blood and lymphatic vessels. The aim of our study was to investigate the immunolocalization and immunoexpression of ERalpha in the ovaries of postmenopausal women. The study involved 50 postmenopausal women who had their ovaries removed by laparotomy due to non-neoplastic diseases of the uterus. The women were divided into 3 groups (A, B, and C) depending on the time that had passed since the last menstruation. Group A consisted of women who had their last menstruation no more than 5 years earlier, in group B menopause occurred 5 to 10 years earlier, group C was composed of patients who had the last menstruation over 10 years earlier. In all the patients concentrations of follicle stimulating hormone (FSH), luteinizing stimulating hormone (LH), estradiol (E2), testosterone (T), androstendione (A) and dehydroepiandrosterone sulphate (DHEAS) in blood plasma were measured. Ovarian tissue was obtained during surgery. For morphological studies, ovaries were fixed in Bouin;s solution and 4% formalin and embedded in paraffin. Morphological analysis was carried out after hematoxylin-eosin (HE) staining. Comparing to groups A and B, the ovaries in group C contained a small number of corpora albicantia located in the medullary part as well as thinned blood vessels and few lymphatic vessels and nerves. For immunoohistochemical expression of ERalpha paraffin-embedded specimens fixed in 4% buffered formalin were used. The sections were next incubated with monoclonal mouse anti-human ERalpha antibody (N 1575 Dako, Denmark). Immunohistochemical nuclear expression of ERalpha in OSE, in epithelial inclusion cysts, in stroma, and in group A also cytoplasmic expression of ERalpha in luteal and paraluteal cells of disappearing corpus luteum were revealed. Immunohistochemical expression of ERalpha seems to decrease in the ovaries of women after menopause.